STUDI PENGAPLIKASIAN APPSHEET SEBAGAI MEDIA PENDUKUNG MONITORING PRAKTIK KERJA LAPANGAN PRODI TEKNIK OTOMOTIF SMK N 5 SURAKARTA - Rasyid Sidik; Muhammad Kholil; Danar Susilo Wijayanto; Ngatou Rohman (Nozel : Jurnal Pendididikan Teknik Mesin, 2024)
The duration of the internship program in Indonesia has changed, from 3 months to 6 months. Increasing the duration of the internship program requires a supportive monitoring model, considering the problem of student attendance and the limited costs of monitoring the internship program. The AppSheet platform is a solution that needs to be developed and implemented as a support tool for student monitoring. The research method uses a qualitative phenomenological, to find out the results of implementing the AppSheet application as an online attendance and recap of the attendance of automotive engineering students at SMK N 5 Surakarta during the internship program from April 1 to September 30, 2023. Observation Interview data and documentation are presented in text form descriptive narrative, through interactive analysis techniques. As a result, the AppSheet application helps teachers monitor student attendance during industrial work practices, makes it easier to detect student absences, and becomes the basis for providing personal and group guidance for students who experience problems during the internship program.